2014
DOI: 10.1093/molehr/gau065
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stimulation using human chorionic gonadotrophin impairs blastocyst implantation and decidualization by altering ovarian hormone levels and downstream signaling in mice

Abstract: Ovarian stimulation induced by follicle-stimulating hormone and human chorionic gonadotrophin (hCG) is commonly used in assisted reproductive technology to increase embryo production. However, recent clinical and animal studies have shown that ovarian stimulation disrupts endometrial function and embryo development and adversely affects pregnancy outcomes. How ovarian stimulation impairs pregnancy establishment and the precise mechanisms by which this stimulation reduces the chances of conception remain unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 81 publications
(109 reference statements)
4
39
0
Order By: Relevance
“…), and previous studies have revealed that steroid hormones are associated with luteinizing hormone and follicle‐stimulating hormone and play key roles in ovarian stimulation and embryo development (Andersen & Ezcurra ; Ezoe et al . ). Although the function of DGKQ is undefined in chickens, it may interact with the sex steroid hormone system to affect egg production traits.…”
Section: Resultsmentioning
confidence: 97%
“…), and previous studies have revealed that steroid hormones are associated with luteinizing hormone and follicle‐stimulating hormone and play key roles in ovarian stimulation and embryo development (Andersen & Ezcurra ; Ezoe et al . ). Although the function of DGKQ is undefined in chickens, it may interact with the sex steroid hormone system to affect egg production traits.…”
Section: Resultsmentioning
confidence: 97%
“…In terms of the mechanism behind the role of estrogen and progesterone in NVP, it has been reported that stimulation with hCG increase serum concentrations of progesterone and estrogen in a mouse model (Ezoe et al, 2014). Progesterone and estrogen can alter gastric rhythms in non-pregnant women increasing gastric intestinal transit time and slowing gastric emptying which may lead to increased nausea and vomiting (Bruce et al, 1978; Lee et al, 2011; Milenov et al, 1973; Walsh et al, 1996).…”
Section: Pathogenesismentioning
confidence: 99%
“…In regularly cycling women, it has been hypothesized that ovarian stimulation with either oral agents or exogenous gonadotropins (Gns) may improve certain defects in the follicular and subsequent luteal phase, resulting in a better endometrial preparation for embryo implantation [17,18]. However, it has also been claimed that ovarian stimulation may lead to decreased endometrial receptivity [3,19,20].…”
Section: Introductionmentioning
confidence: 99%